2019
DOI: 10.1037/per0000333
|View full text |Cite
|
Sign up to set email alerts
|

Examining the triarchic psychopathy measure and comprehensive assessment of psychopathic personality in self-identified offender populations.

Abstract: Despite the clear clinical and forensic importance of psychopathy, definitions of psychopathy and the optimal measurement of the disorder are issues of continued controversy. The present research provides an empirical examination of two self-report instruments indexing recent conceptualizations of psychopathy: the Comprehensive Assessment of Psychopathic Personality–Self-Rating Scale (CAPP-SR) and Triarchic Psychopathy Measure (TriPM). This study provides the first examination of the convergence between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…These findings are further supported by work demonstrating that CAPP symptoms are not only sensitive to PPD but also exhibit high levels of specificity, meaning that they are indicative of PPD in particular, and not personality dysfunction more generally (Kreis et al, 2012). Furthermore, tools utilizing the CAPP model have generally shown moderate to high levels of internal consistency at the domain and total score level within multiple relevant populations (e.g., Danish psychiatric inpatients, Canadian serious and violent offenders, American self-reported offenders, and community members; Dawson et al, 2012; Hanniball et al, 2019 Pedersen et al, 2010; Sellbom et al, 2015). Additionally, CAPP tools have demonstrated convergent validity with other established measures of PPD, such as the Psychopathy Checklist-Revised (PCL-R; Hare, 2003) and its derivatives (Pedersen et al, 2010; Sandvik et al, 2012), as well as with the Triarchic Psychopathy Measure’s (TriPM; Patrick et al, 2009) components of Meanness and Disinhibition (Hanniball et al, 2018), and also exhibit predictive capabilities for violent and nonviolent recidivism that are on par with the PCL-R (Pedersen et al, 2010).…”
Section: Previous Capp Researchmentioning
confidence: 99%
“…These findings are further supported by work demonstrating that CAPP symptoms are not only sensitive to PPD but also exhibit high levels of specificity, meaning that they are indicative of PPD in particular, and not personality dysfunction more generally (Kreis et al, 2012). Furthermore, tools utilizing the CAPP model have generally shown moderate to high levels of internal consistency at the domain and total score level within multiple relevant populations (e.g., Danish psychiatric inpatients, Canadian serious and violent offenders, American self-reported offenders, and community members; Dawson et al, 2012; Hanniball et al, 2019 Pedersen et al, 2010; Sellbom et al, 2015). Additionally, CAPP tools have demonstrated convergent validity with other established measures of PPD, such as the Psychopathy Checklist-Revised (PCL-R; Hare, 2003) and its derivatives (Pedersen et al, 2010; Sandvik et al, 2012), as well as with the Triarchic Psychopathy Measure’s (TriPM; Patrick et al, 2009) components of Meanness and Disinhibition (Hanniball et al, 2018), and also exhibit predictive capabilities for violent and nonviolent recidivism that are on par with the PCL-R (Pedersen et al, 2010).…”
Section: Previous Capp Researchmentioning
confidence: 99%
“…Confirmatory factor analyses and correlation studies have indicated good construct validity of the CAPP model; with large correlations seen between scores from the CAPP and other well validated measures of PPD, as well as support for a broad 'global' psychopathy factor (Hanniball et al, 2019;Kreis et al, 2012;McCuish et al, 2019;Sandvik et al, 2012;Sellbom et al, 2015;. The internal structure of the CAPP has been assessed yielding a three-factor solution with domains representing behavioral, interpersonal, and affective areas of functioning (Hanniball et al, 2021;Kavish et al, 2020).…”
Section: The Comprehensive Assessment Of Psychopathic Personalitymentioning
confidence: 97%
“…For the self-report assessment, the CAPP Lexical Rating Scale (CAPP-LRS) asks participants to self-report the applicability of the 33 CAPP symptoms where each symptom is appended three adjectives as descriptors (Sellbom et al, 2015). Hanniball, Gatner, Douglas, Viljoen, and Aknin (2019) reported high correlations between the CAPP-LRS and other mainstream psychopathy measures such as the TriPM and the Psychopathic Personality Inventory (Lilienfeld & Andrews, 1996; see also Kavish, Schiafo, Sellbom, & Anderson, 2020). However, reliability of the measure is highly dependent on the homogeneity and accuracy of participants’ understanding of the adjectives as well as participants’ insight of their own functioning as described in the adjectives (e.g., “Lacks emotional depth”).…”
Section: Comprehensive Assessment Of Psychopathic Personalitymentioning
confidence: 99%